Tunnel Structure Enhanced Polysulfide Conversion for Inhibiting “Shuttle Effect” in Lithium-Sulfur Battery - Xiaotong Guo; Xu Bi; Junfeng Zhao; Xinxiang Yu; Han Dai (Nanomaterials, 2022)
The Lithium sulfur (Li-S) battery has a great potential to replace lithium-ion batteries due to its high-energy density. However, the “shuttle effect” of polysulfide intermediates (Li2S8, Li2S6, Li2S4, etc.) from the cathode can lead to rapid capacity decay and low coulombic efficiency, thus limiting its further development. Anchoring polysulfide and inhibiting polysulfide migration in electrolytes is one of the focuses in Li-S battery. It is well known that polar metal oxides-manganese oxides (MnO2) are normally used as an effective inhibitor for its polysulfide inhibiting properties. Considering the natural 1D tunnel structure, MnO2 with three kinds of typical tunnel-type were screened to study the effects of the tunnel size on the adsorption capacity of polysulfide. We found that MnO2 with larger tunnel sizes has stronger chemisorption capacity of polysulfide. It promotes the conversion of polysulfide, and corresponding cathode exhibits better cycle reliability and rate performance in the cell comparison tests. This work should point out a new strategy for the cathode design of advanced Li-S battery by controlling the tunnel size.